Understanding Sukuk Market Development: An Overview of Opportunities and Challenges - Nurhanifah, Nita Viviani (Indonesian Journal Publisher, 2024)
Sukuk, as integral Islamic financial instruments, have witnessed substantial growth in recent years, signifying a significant evolution in the Islamic finance domain. This paper delves deeply into the dynamics surrounding the development of the sukuk market, meticulously examining both the opportunities it presents and the challenges it poses. In this study, a qualitative research methodology is employed, consisting of two main approaches: exploration and descriptive analysis. Through an exploratory study and descriptive analysis, data were gathered primarily from online libraries and databases. Through a meticulous synthesis of existing literature and empirical evidence, this research endeavors to furnish a comprehensive understanding of the myriad factors influencing the growth of the sukuk market and the implications for diverse stakeholders involved. By shedding light on the potential of sukuk as a viable investment avenue, while concurrently addressing the regulatory, structural, and market-related obstacles impeding its broader adoption and expansion, this study aims to offer valuable insights.